Study on the effect of reinforcement particle size parameter on Aluminum metal matrix composite reinforced with Alumina particles - Salihah Tan Shilan (Universiti Malaysia Perlis, 2008)
The physical and mechanical properties of different particle sizes of alumina reinforce in aluminum metal matrix composite were investigated. In general, P/M aluminum matrix composites exhibit good levels of mechanical properties compared with those from other alternative manufacturing processes. The processes involved in P/M method were mixing, compaction, and sintering. Before that, the alumina particles size, density and morphology will be analyzed. Process begins with mixing 90 wt% aluminum powder, 10 wt% alumina powder and 1 wt% stearic acid (binder) in the rolling mill at 150 rpm for 4 hours. The mixture will compacted at 150MPa and sinter at 600oC with 5 hours soaking time. Several tests were carried out due to investigate the effect of different particle sizes on physical and mechanical properties of alumina metal matrix composite. The test analysis was consists of microstructure, hardness, density, porosity, and corrosion behavior of the composites. Result pattern shows Alumina with particles size 1 µm was distributed uniformly in Al matrix after sintering process and tends to harden the AMC. More fine particles was increased the AMC hardness due to the uniformity of alumina particles distribution in Al matrix. As increasing the particles size, the density tends to increase. Corrosion of the composites intensifies as the increasing in porosity. Occurring porosity has lead to corrosion initiated and liable to severe attack.